Sulfonated graphene-modified electrodes for enhanced capacitive performance and improved electro-oxidation of hydrogen peroxide - Daripa, S.; Singh, V.K.; Prakash, O.; Maiti, P.; Kuila, B.K.; Das, S. (Elsevier B.V., 2020)
Electrochemical studies of graphene oxide (GO) containing sulfur-oxygen functional group (sulfonated graphene) and its application as electrode material for supercapacitor and electrocatalytic oxidation of H2O2 are demonstrated in this report. The sulfonated graphene (SGO) was synthesized using uniform heating of a homogeneous mixture of GO and ammonium sulfate at an elevated temperature ∼245 °C and characterized using FTIR, UV–Vis spectroscopy, and transmission electron microscopy. The electrochemical characterizations showed that the SGO exhibit the capacitance value as high as 248 F/g at current density 0.15 A/g along with superior cyclic stability (∼80% retention of cyclic stability after 8000 cycles). Also, SGO showed excellent electrocatalytic activity towards H2O2 oxidation and further, an electrochemical sensor for H2O2 detection was fabricated in an aqueous medium with ultra-low detection limit and high sensitivity. The oxidation current was found to be increased linearly with H2O2 concentration in the range of 10–100 μM and 0.1–1 mM with a detection limit of 10.44 μM and 0.038 mM respectively. The detailed kinetic study, including evaluation of kinetic parameters of the electro-oxidation process was also performed from the cyclic voltammetry study. We believe that this work will pave pathways towards diverse functional applications including electrocatalysis, non-enzymatic sensing in medical devices, energy harvesting and storage. © 2020 Elsevier B.V.
Keywords: Sulphonated-graphene; Supercapacito; Electrooxidation; Kinetics; Non-enzymatic sensors